Bidirectional Role of Pericytes in Ischemic Stroke - Jingya Xu; Weiming Zhao (Brain Sciences, 2025)
Ischemic stroke (IS) is a disease characterized by disruption of blood flow to the brain, resulting in damage to brain tissue and neurological deficits. The high incidence of IS and the complexity of the underlying pathophysiology of IS have led to the need for further therapeutic development. It has been found that pericytes are indispensable multifunctional cells, which can coordinate multiple biological processes, and play a vital role in the development of IS. The purpose of this review is to provide a detailed overview of the role of pericytes in regulating vascular blood flow, maintaining BBB, regulating immune response, and promoting intracerebral fibrosis during the pathophysiological process after IS, which have dual effects on intracerebral recovery after IS. Finally, the article summarizes the current strategies targeting pericytes for the treatment of IS.